Indexation and Displacement: Spiritain Missions in the central highlands of Angola - Dulley, Iracema (Africana Studia, 2020)
This paper deals with two complementary aspects of Catholic missions in Angola: the relationship between the church, the colonial state and those legally classed as indígenas (natives); and the architecture of the Catholic mission, in which catechists played a major role. It focuses on the social context of missions in the central highlands and argues that while the relation between the state and the church was inseparable from the “receptivity” to Christianity attributed to the inhabitants of the central highlands, the mission was established in the region not only due to its relation to the colonial state, but also because of the way in which the missionary project was connected to local institutions. In other words, the Catholic mission in Angola must be understood as a process in which a convention is both created and disputed through the indexation of languages, rituals, and institutions. Keywords: Catholic missions, Angola, colonial state, catechists, indexation.